Tourist Villages and Resorts in the Qarabulli Area Between Randomness and Planning and Their Role in Reinforcing Libyan Identity (Journal of Libya for geographical studies, 2025)
This study examines the reality of villages and tourist resorts in the Qarabulli area, one of Libya’s most prominent coastal regions due to its natural and geographical features. The research highlights the increasing expansion of tourism projects in the area, much of which has occurred in an unplanned and random manner due to the absence of proper urban planning, weak oversight, and overlapping responsibilities among relevant authorities.The study also addresses the impact of this unregulated expansion on the coastal environment and urban landscape, in addition to the limited integration of Libyan cultural and architectural elements. Many resorts were found to adopt foreign architectural styles that fail to reflect Libyan identity, thus limiting their role in reinforcing national identity or promoting cultural tourism.The study concludes with a call for integrated planning policies based on sustainability principles, aiming to strengthen Libyan identity in tourism design. It also recommends encouraging well-regulated investment and empowering local communities to participate in shaping the future tourism vision for the region.
Keywords: Resort; identity; tourism; beach; environment